2012
DOI: 10.1182/blood-2011-12-396101
|View full text |Cite
|
Sign up to set email alerts
|

IL-5 promotes induction of antigen-specific CD4+CD25+ T regulatory cells that suppress autoimmunity

Abstract: Immune responses to foreign and selfAgs can be controlled by regulatory T cells (Tregs) expressing CD4 and IL-2R␣ chain (CD25). Defects in Tregs lead IntroductionBoth Ag-specific 1 and naive regulatory T cells (Tregs) 2-4 that control immune responses are mainly CD4 ϩ CD25 ϩ T cells 5 expressing transcription factor FOXP3. 6 Autoimmunity occurs with the breakdown in immune tolerance to self-Ag and can be because of a failure of natural Tregs (nTregs) produced by the thymus which prevent spontaneous autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 50 publications
7
110
0
Order By: Relevance
“…To our knowledge, this study provides the first evidence that IL-5 may have a key role in helminth-induced attenuation of autoimmunity. Consistent with these findings, it has been reported that administration of recombinant IL-5 ameliorated experimental autoimmune neuritis in rats (42). However, the protective effect of exogenously administered IL-5 in this model appeared to be dependent on Tregs (42), suggesting species-specific differences in the response to IL-5.…”
Section: Discussionsupporting
confidence: 81%
“…To our knowledge, this study provides the first evidence that IL-5 may have a key role in helminth-induced attenuation of autoimmunity. Consistent with these findings, it has been reported that administration of recombinant IL-5 ameliorated experimental autoimmune neuritis in rats (42). However, the protective effect of exogenously administered IL-5 in this model appeared to be dependent on Tregs (42), suggesting species-specific differences in the response to IL-5.…”
Section: Discussionsupporting
confidence: 81%
“…In particular, treatment of experimental autoimmune neuritis with IL-5 markedly reduced the infiltration of CD4 + (Th1 and Th17) and CD8 + T cells, and macrophages in nerves with expansion of antigen-specific CD4 + CD25 + FoxP3 + Tregs. Moreover, the depletion of CD25 + Tregs or blocking of IL-4 abolished the benefits of IL-5 treatment [99]. Overall, the study suggested IL-5 therapy may be able to induce antigen-specific tolerance in autoimmune disease.…”
Section: Interleukin-5mentioning
confidence: 81%
“…Tran et al [99] have shown that IL-5 is able to promote the induction of antigen-specific CD4 + CD25 + Tregs that suppress autoimmunity. In particular, treatment of experimental autoimmune neuritis with IL-5 markedly reduced the infiltration of CD4 + (Th1 and Th17) and CD8 + T cells, and macrophages in nerves with expansion of antigen-specific CD4 + CD25 + FoxP3 + Tregs.…”
Section: Interleukin-5mentioning
confidence: 99%
“…Ts2 cells have increased antigenspecific suppressor potency in vivo and in vitro, suppressing at ,1:10, whereas fresh nTregs only fully suppress at $1:1. We found that treatment with IL-5 promoted these cells to control autoimmunity (65) and transplant rejection (57). Tregs controlling Th2 responses express the transcription factor IRF4 (110).…”
Section: Il-4 Promotes Antigen-specific Tregsmentioning
confidence: 87%
“…They enhance antigen-specific suppressor capacity and can be further activated by specific antigen and IL-5 in the absence of IL-4 to Th2-like Tregs that have a very potent antigen-specific suppressor capacity. (57,65).…”
Section: Th2 Cellsmentioning
confidence: 99%